Vitamin D supplementation and its impact on leptin and interleukin-6 in women following religious intermittent fasting: a controlled study - Karras, Spyridon N.; Michalakis, Konstantinos; Kypraiou, Maria; Al Anouti, Fatme; Fakhoury, Hana; Annweiler, Cedric; Pilz, Stefan; Anemoulis, Marios; Vlastos, Antonios; Haitoglou, Costas; Riedmann, Uwe; Georgopoulos, Neoklis; et al. (Frontiers in Endocrinology, 2025)
BackgroundVitamin D deficiency is highly prevalent in populations following intermittent or religious fasting, particularly Orthodox nuns with limited sun exposure and dietary restrictions. Vitamin D may modulate adipokines and inflammatory markers, but clinical evidence remains inconsistent.ObjectiveTo investigate the effects of vitamin D supplementation on interleukin-6 (IL-6) and leptin concentrations in Orthodox nuns compared with non-supplemented controls.MethodsIn this controlled, non-randomized trial, 33 Orthodox nuns received oral vitamin D3 supplementation (2,500 IU/day) for 16 weeks, while 42 age-matched women following Orthodox intermittent fasting served as controls. Anthropometric indices and serum concentrations of 25-hydroxyvitamin D [25(OH)D], IL-6, leptin, parathyroid hormone, insulin, and C-reactive protein were measured at baseline and follow-up.ResultsAt baseline, serum 25(OH)D concentrations were lower in the supplementation group compared with controls (23.4 ± 10.1 vs. 27.7 ± 11.2 ng/mL, p = 0.043). After 16 weeks, 25(OH)D increased significantly in the supplementation group (23.4 ± 10.1 vs. 33.9 ± 11.0 ng/mL, p < 0.001), with no change in controls (27.7 ± 11.2 vs. 28.5 ± 12.2 ng/mL, p = 0.941). Leptin showed a non-significant decrease in the supplementation group (24.4 ± 18.3 vs. 21.9 ± 13.5 ng/mL, p = 0.215), whereas in the controls, it remained unchanged (23.21 ± 14.67 vs. 24.05 ± 13.89 pg/mL, p = 0.365). IL-6 did not change significantly in either group. Exploratory multivariable regression did not reveal significant predictors of leptin changes.ConclusionsVitamin D supplementation effectively corrected deficiency but did not significantly affect leptin or IL-6 concentrations. These results highlight the need for larger and longer studies to further clarify the immunometabolic impact of vitamin D supplementation in women practicing intermittent fasting.